Effect of the inner cylinder endwall shape on the stability of Taylor-Couette flow - Daimallah, Ahmed; Lebbi, Mohamed (Zielona Góra: Uniwersytet Zielonogórski)
The current research aims to study how changing the endwall shape of the inner cylinder affects the appearance of Ekman cells and the onset of Taylor vortices. A two-dimensional numerical method simulates the flow between two concentric cylinders, with the inner cylinder rotating while the outer cylinder and the upper and lower endwalls remain at rest. The method of solving the Navier-Stokes equations for incompressible viscous flows is provided by the Ansys Fluent software, which is based on the finite volumes method.
Keywords: Taylor-Couette flow; hemispherical endwall shape; Ekman cells; Taylor vortices